EMPOWERING THE CHARACTER EDUCATION FOR INDONESIAN PEOPLE IN FACING ASEAN ECONOMIC COMMUNITY (AEC) - Sri Wahyuningsih (Proceedings Education and Language International Conference, 2017)
This paper mainly describes the importance of empowering the character education for Indonesian people in order to face Asean Economic Community (AEC). Nowadays, the Indonesian citizens have played a dominant role in meeting the Asean Community. Indeed, they will be the actors participating and implementing a number of public policies in Indonesia. As a matter of fact, AEC is the realization of the end goal of economic integration to deepen and broaden the economic integration through existing and new strategies using the principles of an open, inclusive and market-driven economy. Considering this, the existence of AEC can be both an opportunity and challenge for the Asean countries including Indonesia. The opportunity of AEC is it can be a single market and its productions will be more dynamic and accessible. On the other hand, Indonesia should have good preparations and numerous strategies to achieve the goal of AEC. Those strategies cover accelerating the regional integration in the main sectors, facilitating skilled labor and talents, fostering the nationality among Indonesian people, and etc. In accordance with the enforcement of nationality among Indonesian people, it is necessary to empower the character education for the Indonesian people since at an early age considering the values of character among teenagers have been lost. The implementation of the character education done within the family, school and community is considerably effective to enhance the Asean Economic Community in line with the principles of global citizenship.Keywords: Asean Economic Community, Character Education, Indonesian People